Research on Enhancing the Comprehensive Abilities of College Students from the Perspective of Home School Collaboration - Lu, Yunlyu; Emily Sarmiento (International Journal of Social Sciences and Public Administration, 2024)
This study aims to explore the impact of home school collaboration on the comprehensive ability improvement of college students. By analyzing the roles and functions of parents, schools, and society in cultivating students’ comprehensive abilities, this paper points out the importance of the tripartite collaboration between home, school, and society in the cultivation of college students, and proposes a series of targeted suggestions. The study used questionnaire surveys and empirical analysis to reveal the effectiveness of home school collaboration in enhancing college students’ learning ability, practical ability, innovation ability, and social adaptation ability. Finally, this article summarizes the significant impact of home school collaboration on enhancing the comprehensive abilities of college students and provides recommendations for the formulation of relevant policies.